Systematic Literature Review of Environmental Impact Assessments - Nurhadi Kumayza, Toni; Pramusinto, Agus; Widaningrum, Ambar (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2024)
This article provides a systematic literature review (SLR) of Environmental Impact Assessments(EIA) in Public Administration (PA), analysing scholarly articles published between 1971 and 2023 through bibliometric and qualitative methods. Using VOSviewer for quantitative insights and qualitative analysis, the study comprehensively examines the evolution and thematic trends of EIA research. It identifies critical themes like public participation, regulatory frameworks, and environmental integration that shape EIA practices. Analysing 287 journal articles, the review shows that public participation is a dominant theme, reflecting a shift toward inclusive, participatory governance. This transition includes climate change considerations in EIA processes and the use of advanced technologies like remote sensing and AI to improve accuracy and efficiency. EIA research has evolved from strict regulatory compliance to broader, tech-enhanced, participatory approaches. This SLR tracks EIA studies' historical progression and diversification, revealing emerging trends and gaps while laying a foundation for future research. It offers valuable insights into environmental assessment and public policy, contributing significantly to environmental management discourse.